1994
DOI: 10.1590/s0034-89101994000600007
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças no padrão de alimentação da população urbana brasileira (1962-1988)

Abstract: Contemporary changes in food consumption patterns in urban areas of Brazil are described. The main data sources are two national food expenditure surveys undertaken in the early 60's and late 80's (1961-62 and 1987-88) and one national food intake survey undertaken in the mid-70's (1974-75). The analysis is restricted to the seven metropolitan areas represented in the three surveys. Food patterns are described on the basis of the relative consumption of different food groups, proportion of energy from carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
89

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 8 publications
1
21
0
89
Order By: Relevance
“…Mondini & Monteiro 5 , assessing the dietary pattern of the Brazilian population, also reported that the contribution of fruits to total calorie intake in Brazil decreased from 3.8% in 1962 to 2.5% in 1988. During the 1990s, Monteiro et al 6 showed that there had been an increase in consumption of alcoholic beverages and foods of animal origin, while the share of fruits, greens, and other vegetables in total diet remained practically unchanged.…”
Section: Introductionmentioning
confidence: 97%
“…Mondini & Monteiro 5 , assessing the dietary pattern of the Brazilian population, also reported that the contribution of fruits to total calorie intake in Brazil decreased from 3.8% in 1962 to 2.5% in 1988. During the 1990s, Monteiro et al 6 showed that there had been an increase in consumption of alcoholic beverages and foods of animal origin, while the share of fruits, greens, and other vegetables in total diet remained practically unchanged.…”
Section: Introductionmentioning
confidence: 97%
“…As dietas brasileiras normalmente são pobres em fibras, como observado em vários trabalhos, que também utilizaram a amostragem em porção em duplicata [12].…”
Section: Considerando Os Valores Preconizados Pelas Novas Drisunclassified
“…Em decorrência, passam a coexistir, simultaneamente, quadros de subnutrição e de ingestão desbalanceada 18 . No Brasil -principalmente na região Sudeste -a evolução do consumo alimentar nas últimas três décadas configura-se como um exemplo dessas alterações 15 ; para as sete maiores áreas metropolitanas do País são descritas relevantes modificações na composição das refeições domiciliares: a crescente substituição de proteínas vegetais por animais e de carboidratos por gorduras 14 .…”
Section: Complementação Alimentarunclassified